Model STAD dan NHT dengan Pendekatan Labirin untuk Meningkatkan Keterampilan Berpikir Kritis, Kemampuan Kolaborasi, dan Pemahaman Konsep Virus dan Perannya pada Mata Pelajaran Biologi SMK - Rosita Segetmena; Nancy Susianna; Nerru Pranuta Murnaka (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
21st-century Biology learning emphasizes the importance of developing critical thinking skills, collaboration, and conceptual understanding as key competencies for students. However, learning about viruses and their roles still faces challenges due to the abstract nature of the concepts and the dominance of memorization-based approaches. This study aims to analyze the effect of implementing the Students Team Achievement Division (STAD) and Numbered Heads Together (NHT) models based on the Labyrinth approach on students’ critical thinking skills, collaboration abilities, and conceptual understanding in vocational high schools. The results showed that the integration of STAD, NHT, and the Labyrinth approach significantly improved all three aspects. The improvement was reflected in students’ analytical abilities, group interactions, and understanding of virus concepts based on statistical tests conducted before and after the learning process. These findings indicate that exploratory-based cooperative learning can create active, contextual, and student-centered learning experiences. The novelty of this study lies in the integrative learning design that simultaneously optimizes cognitive and social aspects.